Temporal dynamics of volatile fatty acids profile, methane production, and prokaryotic community in an in vitro rumen fermentation system fed with maize silage - Dhakal, Rajan; Neves, André Luis Alves; Sapkota, Rumakanta; Khanal, Prabhat; Ellegaard-Jensen, Lea; Winding, Anne; Hansen, Hanne Helene (Frontiers in Microbiology, 2024)
Anaerobic in-vitro fermentation is widely used to simulate rumen kinetics and study the microbiome and metabolite profiling in a controlled lab environment. However, a better understanding of the interplay between the temporal dynamics of fermentation kinetics, metabolic profiles, and microbial composition in in-vitro rumen fermentation batch systems is required. To fill that knowledge gap, we conducted three in-vitro rumen fermentations with maize silage as the substrate, monitoring total gas production (TGP), dry matter degradability (dDM), and methane (CH4) concentration at 6, 12, 24, 36, and 48 hours in each fermentation. At each time point, we collected rumen fluid samples for microbiome and volatile fatty acids (VFA) analysis in each time point. Amplicon sequencing of 16S rRNA genes (V4 region) was used to profile the prokaryotic community structure in the rumen during the fermentation process. As the fermentation time increased, dDM, TGP, VFA concentrations, CH4 concentration and yield (mL CH4 per g DM at Standard Temperature and Pressure (STP)) significantly increased. For the dependent variables CH4 concentration and yield as well as independent variables TGP and dDM, polynomial equations were fitted. These equations explained over 85% of the data variability (R² > 0.85), and suggests that TGP and dDM can be used as predictors to estimate CH4 production in rumen fermentation systems. Microbiome analysis revealed a dominance of Bacteroidota, Cyanobacteria,